Assessment of Historical and Projected Droughts at Siliana Watershed Catchment (Northern Tunisia) - Abir Mlayah; Ahmed Skhiri; Slaheddine Khlifi (African Journal of Advanced Pure and Applied Sciences, 2024)
Drought is one of the complex weather events affecting water resources and socio-economic conditions in arid environments that would be most exacerbated by climate change. Drought assessment can be useful in implementing strategies and measures to mitigate drought. This study focuses on the potential use of the Standardized Precipitation Index (SPI) based on precipitation and the Martonne Aridity Index (MAI) based on temperature to reproduce the meteorological and hydrological droughts observed in the Siliana watershed. The determination of these indices was evaluated for different time scales (monthly, seasonal, biannual, and annual) during the period 1960–1989, considered as the reference period, and climate projections to 2041–2070, as a mid-term period for climate change. Thirteen rain stations were selected for this work, spread throughout the Siliana basin. The calculation of SPI at different times was used to provide drought characterization maps using inverse distance interpolation. The SPI analysis shows a good agreement with the drought episodes. SPI was also used to study the temporal evolution of drought and its severity. The most severe droughts in the basin occurred during the 1980s–89. The intensity of droughts was mild to moderate, despite the presence of severe to extreme droughts in 1987.